Experimental study on pulverized coal combustion preheated by a circulating fluidized bed: Preheating characteristics for peak shaving. (15th September 2022) - Zhu, Shujun; Hui, Jicheng; Lyu, Qinggang; Ouyang, Ziqu; Liu, Jingzhang; Zhu, Jianguo; Zeng, Xiongwei; Zhang, Xiaoyu; Ding, Hongliang; Liu, Yuhua; Zhang, Jiahang
Highlights: Preheating of pulverized coal fosters flexible peak shaving. Preheating-combustion technology improves the low-load combustion stability. Two bases for determining the stabilization after load changes are discussed. Optimal load step range exists for a high load-change rate. Abstract: With the continuous growth of renewable energy, the electricity market is increasingly targeting flexibility and deep-peaking capabilities for coal-fired generation. In this study, the low-load operation and rapid load-change characteristics of pulverized coal combustion are explored on a 1 MWth test platform, based on a promising preheating-combustion technology. At loads of 25% and 35%, excellent gas–solid flow characteristics and stable operating parameters such as temperature and pressure drop can be achieved in the pre-circulating fluidized bed. After preheating, pulverized coal is converted into preheated coal gas with a high calorific value and preheated char with a high physical sensible heat and ample porous structure. These greatly improved the low-load ignition and combustion stability in the combustion chamber. Moreover, two bases for determining the stabilization after load change were discussed: the preheating temperature and the preheated coal gas. The load-change rates at ramp-up were generally higher than those at ramp-down within the same step ranges. The optimal step range for a higher load-change rate during load ramp-up/down was found, and the maximum load-change rate of 3.75%/min was achieved. Furthermore, the step range of the fuel mass flow rate had a positive effect on counteracting the thermal inertia at the load ramp-down. This study verifies a feasible technology for peak shaving of coal-fired power generation, and it can provide certain theoretical guidance for future engineering applications.